Developmental Strategy of Suku Dayak Meratus Juhu Village South Borneo Province - Mohamad Sukeri Khalid; Nurul Azkar (Jurnal Penelitian Kesejahteraan Sosial, 2014)
Marginalization process on Suku Dayak Meratus, South Borneo Province, during a new order has slightly change then in reformation era government, though an experiment of being marginalized in a long period of time loomed traumaticfeeling, so they have been precarious and tending persistent against government policy, included the policy of reformation government. But behind all of the conditions, Suku Dayak Meratus Juhu Village living in tropical forest of Meratus Hill have defense strategy and selves development to enhance their welfare, and still keep traditional value related to their environment natural prevention.